The temporal relationship between glucose-corrected serum sodium and neurological status in severe diabetic ketoacidosis. Issue 1 (4th October 2010) - Durward, Andrew; Ferguson, Lee P; Taylor, Dan; Murdoch, Ian A; Tibby, Shane M
Abstract : Objective: Cerebral oedema is a potentially devastating complication of diabetic ketoacidosis (DKA). The relationship between osmolar changes, acid–base changes and development of cerebral oedema during therapy is unclear. Design: Retrospective cohort study on 53 children with severe DKA (mean pH at presentation 6.92±0.08). Cerebral oedema was diagnosed using neurological status, response to osmotherapy, and neuroimaging, and classified as: early (occurring ≤1 h after presentation, n=15), late (1–48 h, n=17) or absent (controls, n=21). The temporal profiles for various osmolar and acid–base profiles were examined using a random coefficients fractional polynomial mixed model, adjusted for known risk factors. Results: The three groups could not be differentiated by demographic, osmolar or acid–base variables at presentation. All osmolar and acid–base variables showed non-linear temporal trajectories. Children who developed late onset oedema showed dramatically different temporal profiles for effective osmolality and glucose-corrected serum sodium (both p<0.001). Glucose-corrected sodium provided better qualitative discrimination, in that it typically fell in children who developed late oedema and rose in controls. The maximum between-group difference for both variables approximated the median time of clinical cerebral oedema onset. Blood glucose and acid–base temporal profiles did not differ between the groups. Late onset oedema patients received more fluid in the first 4 h, but this did not influence the osmolar or glucose-corrected sodium trajectories in a predictable fashion. Conclusions: Glucose-corrected serum sodium may prove a useful early warning for the development of cerebral oedema in DKA.